2020
DOI: 10.1186/s12933-020-01149-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of the ankle-brachial index combined with the percentage of mean arterial pressure at the ankle to improve prediction of all-cause mortality in type 2 diabetes mellitus: an observational study

Abstract: Background Peripheral artery disease (PAD) in the lower extremities is a common complication of type 2 diabetes and has been shown to be associated with mortality. The ankle-brachial index (ABI) is a simple noninvasive method to screen PAD, but this method has limited sensitivity. We hypothesized that using the percentage of mean arterial pressure (%MAP) in combination with the ABI would improve the prediction of mortality. Methods W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 60 publications
0
10
0
1
Order By: Relevance
“…ROC results revealed that the combination of ABI and baPWV may improve risk classification in predicting all-cause and expanded CVD mortality in patients with T2DM. ABI and baPWV are simple, non-invasive, economical, and realistic measures that have become increasingly important in predicting mortality [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] . Most studies exploring the associations of ABI and/or baPWV with mortality in T2DM population [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] only considered ABI alone [28][29][30][31][32][33][34][35][36][37]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ROC results revealed that the combination of ABI and baPWV may improve risk classification in predicting all-cause and expanded CVD mortality in patients with T2DM. ABI and baPWV are simple, non-invasive, economical, and realistic measures that have become increasingly important in predicting mortality [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] . Most studies exploring the associations of ABI and/or baPWV with mortality in T2DM population [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] only considered ABI alone [28][29][30][31][32][33][34][35][36][37]…”
Section: Discussionmentioning
confidence: 99%
“…Only two works considered baPWV alone 43,44 , and another two simultaneously considered ABI and baPWV 45,46 . As a consequence, the findings on the association between ABI and mortality were inconsistent [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] . Significant associations were observed in some studies [28][29][30][31][32][33][34][35][36][37][38][39][40] but not in others 41,42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic retinopathy was reported to be associated with eGFR variability and predictive of all-cause mortality in patients with type 2 DM [40,41]. Peripheral artery disease (PAD) was also reported to be associated with CKD [42], and a high-risk PAD is predictive of all-cause mortality in patients with type 2 DM [43]. Moreover, Zhang et al [44] verified that CKD was associated with a reduction in left ventricular function and strain based on cardiac magnetic resonance imaging in patients with type 2 DM.…”
Section: Discussionmentioning
confidence: 99%
“… 29 There is a lack of investigation to assess the relationship between %MAP and glucose variability. Since a combination of low ABI and high %MAP carries a high mortality risk in patients with DM, 30 we hypothesized that glucose variability is associated with ABI and %MAP in patients with DM. Therefore, this screening study investigated whether glucose variability, as estimated by the standard deviation (SD) of annual fasting plasma glucose, is significantly associated with PAD, reflected by either high %MAP or low ABI, in patients with DM.…”
Section: Introductionmentioning
confidence: 99%